LE SPRAT (SPRATTUS SPRATTUS L.) DU LITTORAL ROUMAIN DE LA MER NOIRE - Cautis, Ileana (Cercetări Marine - Recherches Marines, 2026)
The paper is a synthesis of the results of researches carried out over the 1956-1969 period on various aspects of sprat. (Sprattus sprattus L.) biology; this fish is caught near the Romanian Black Sea coast. The structure of the population living in this area is also determined and the parameters showing the characteristics of this population and its dynamics are given. Some correlations are established that can be used as elements in drawing up prognoses. The particularities inducing high shifts in sprat fishing near the Romanian Black Sea coast as well as those determining the restoration of the stocks are discussed